Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
Step-by-step explanation:
(3x + 1)/x = 1/(x -3) Cross multiply
(3x + 1)(x - 3) = x Remove the brackets. Use FOIL
f:3x*x = 3x^2
o:3x*(-3) = -9x
i:1*x = x
L : 1 * - 3 = -3
FOIL: 3x^2 -9x +x - 3
FOIL: 3x^2 - 8x - 3
3x^2 - 8x - 3 = x Subtract x from both sides
3x^2 - 8x -x - 3 = 0 Combine
3x^2 - 9x - 3 = 0 Factor
It's rather ugly. I had to use the quadratic equation
a = 3
b = - 9
c = - 3
x1 = 3.3
x2 = - 0.3
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.